Viaggio a Colonia. Un breve confronto con la psichiatria internazionale sugli esordi psicotici - Elena Pappagallo; Alice Masillo; Elena Monducci; Marco Armando; Paolo Fiori Nastro (Il sogno della farfalla, 2009)
This article deals with the experiences of a group of university psychiatrists and young doctors in training at the Early Recognition and Intervention Center for Mental Crises (FETZ) in Cologne. The peculiarity of FETZ is that it deals with young people before the onset of psychosis, in a prodromic phase. The diagnostic methodology used to identify the presence of prodromic symptoms is based on the concept and definition of “basic symptom”. Basic symptoms represent the “basis” of a psychotic pathology and are defined as symptoms which are labelled as subjective, expressions of an underlying biological alteration. The group of symptoms with a cognitive basis (COGDIS) has demonstrated to have a positive predictive value of the development of psychosis at around 70%; some of these, however, seem to also be characteristics of full blown psychosis. Among the manifold reflections triggered off in the face of this theoretical and diagnostic picture, the authors have taken on the problem of succeeding in identifying more precocious and indicative psychopathological nuclei in the face of a more difficult possibility of objectivisation.